Semantic juxtaposition in poem of Sad Yasin Uosef - Yadollahi Farsani, Abbass; Kazim Al ghanimi, Rahim Zayer (Journal of Human Sciences, 2023)
This study is concerned with the semantic juxtaposition of the meaning, and the interest is not limited to the utterance, the sentences, and the structure only, Rather, he transcends it to the juxtaposition of significance between the texts of poetic texts, and what it can give of rooting for the poetic theme (the subject), We have noticed the emergence of the theme of the open, starting with the title of the group, "Trees Breathing in the Open". It focuses on the titles of some of its texts, but the "theme of emptiness" was consulted in the poetic texts once, with an explicit wording, embodied of thematic focus that will attract the recipient to it. And dealing with its inputs and outputs (causes and results), considering being alone or naked as a coercive robbery of the necessities of life. What results from this emptiness of self-disgrace, reflects negatively on the structure of the human psyche.